The study of long noncoding RNA TUG 1 and ZEB2-AS1 expression in newly diagnosed Egyptian adult acute myeloid leukemia patients - Amira Mohamed Noureldin Abdelrahman; Safia Mohammed Diab; Howyda Moh. Kamal Shabaan; Mai Nasser Abdelmomen Ahmed; Reem Nabil (Egyptian Journal of Medical Human Genetics, 2023)
Abstract Background The hematopoietic malignancy acute myeloid leukemia is a fatal disease with poor clinical prognoses. Long non-coding RNA taurine-upregulated gene1 (lncRNA TUG1) and zinc finger E-box binding homeobox 2 antisense RNA1 (lncRNA ZEB2-AS1) are reported to participate in the development and progression of different types of malignancies. The goal of the current study was to evaluate the prognostic value of the lncRNAs TUG1 and ZEB2-AS1 as well as their various expression patterns in newly diagnosed Egyptian adult acute myeloid leukemia patients. Methods We assessed the expression levels of both lncRNA TUG1 and lncRNA ZEB2-AS1 using the quantitative real-time reverse transcription polymerase chain reaction technique (qRT-PCR) in 80 newly diagnosed AML patients and 20 healthy subjects. Results lncRNA TUG1 expression was significantly higher in the AML cases compared to the controls (P < 0.001), whereas lncRNA ZEB2-AS1 expression was considerably lower in the AML cases in comparison with the controls (P < 0.001). The expression levels of the lncRNAs ZEB2-AS1 and TUG1 exhibited a significantly positive association in the AML group (P < 0.001). There was no difference in overall survival (OS) and disease-free survival (DFS) between the groups with low and high lncRNA TUG1 expression (P = 0.139 and 0.918, respectively). Furthermore, the AML cases with higher lncRNA ZEB2-AS1 expression levels had shorter DFS than patients with lower lncRNA ZEB2-AS1 expression levels (P = 0.014), while OS did not significantly differ between the studied cases with lower and higher lncRNA ZEB2-AS1 expression (P = 0.589). Conclusion Overexpression of lncRNA TUG1 could serve as a diagnostic biomarker for Egyptian adult AML cases, while lncRNA ZEB2-AS1 high expression could be regarded as an indicator of poor outcome in Egyptian adult AML studied cases.